Information Transfer through the Spontaneous Baroreflex in Healthy Humans - Porta, A.; Catai, A. M.; Takahashi, A. C. M.; Magagnin, V.; Bassani, T.; Tobaldini, E.; Montano, N. (Methods of Information in Medicine, 2010)
Objectives: This study assesses the information transfer through the spontaneous baroreflex (i.e. through the pathway linking systolic arterial pressure to heart period) during an experimental condition soliciting baroreflex (i.e. head-up tilt).Methods: The information transfer was calculated as the conditional entropy of heart period given systolic arterial pressure using a mutual neighbor approach and uniform quantization. The information transfer was monitored as a function of the forecasting time k.Results: We found that during head-up tilt the information transfer at k = 0 decreased but the rate of rise of information transfer as a function of k was faster.Conclusions: We suggest that the characterization of the information transfer from systolic arterial pressure to heart period might complement the traditional characterization of the spontaneous baroreflex based on transfer function analysis.
Keywords: Information transfer; cross-conditional entropy; baroreflex; autonomic nervous system; cardiovascular control